Criminological Review Of Article 365 Kuhp On The Crime Of Theft Accompanied By Violence In Sorong City - Ramadhan, Syahrul; Sokhib Naim; Hasriyanti Hasriyanti (Journal of Law Justice (JLJ), 2024)
This study aims to identify the factors causing the crime of theft accompanied by violence in the Sorong City Police area and analyze the countermeasures made by the police against these cases, in accordance with Article 365 of the Criminal Code.The research method used is empirical method by collecting primary data from the field and secondary data from relevant written legal materials. The results showed that factors such as economy, environment, education, alcohol (Miras), unemployment, association, and victim negligence significantly contributed to the increase in cases of theft accompanied by violence in the area. Countermeasures carried out by the police include preventive strategies such as blupatroli, socialization through Bhabinkamtibmas, and strengthening the environmental security system. In addition, repressive efforts involving rigorous investigation and prosecution are also applied in accordance with applicable legal provisions to handle these cases.